Treatment Patterns, Health Care Resource Utilization, and Cost in Patients with Myelofibrosis in the United States. (4th February 2022) - Copher, Ronda; Kee, Arianna; Gerds, Aaron
Abstract: Background: This study analyses treatment patterns, health care resource utilization (HCRU), and costs in patients with myelofibrosis (MF) and a subgroup treated with ruxolitinib (RUX). Materials and Methods: Treatment patterns, all-cause and MF-related HCRU, and costs were analyzed in adults with MF with continuous enrollment in a commercial or the Medicare Advantage health plan in the pre-index period, defined as the 12 months immediately prior to the index date (date of primary or secondary MF diagnosis), and the post-index period, defined as ≥6 months following the index date. In a subgroup analysis, outcomes were analyzed in patients treated with optimal RUX (OPT RUX, ≥30 mg) and suboptimal RUX (SUB RUX, <30 mg) in the pre-index RUX period, defined as the 3 months immediately prior to the index RUX date (first date for an RUX claim), and the post-index RUX period, defined as ≥6 months following the index RUX date. Results: Of 2830 patients with an MF diagnosis, 1191 met eligibility requirements. The median age of patients was 72 years, 54% were male, and comorbidities were frequent. Sixty percent of patients received ≥1 line of therapy (LOT), of which 46% ( n = 331) had ≥2 LOTs during the post-index MF period. Costs increased considerably 6-month pre-index to 6-month post-index (all-cause: cause ($24, 216 to $48, 966) and MF-related ($16, 502 to $39, 383), driven by inpatient stays and pharmacy costs. In the subgroup analysis, patients treated with RUX ( n = 495) experienced significant disease burden and high costs, regardless of dose. A shorter duration of therapy and a higher rate of discontinuation were observed in patients treated with SUB RUX ( n = 191) versus OPT RUX ( n = 304). Conclusion: These findings suggest a significant disease and economic impacts associated with MF patients that persists with RUX therapy, highlighting the need for additional therapeutic options for MF. Abstract : Myelofibrosis leads to significant resource utilization and costs for patients and the US health care system. This article describes treatment patterns, health care resource utilization, and costs associated with myelofibrosis and in a subgroup of patients who were treated with ruxolitinib.